Design of Next-Generation 4D Mask Pack - Jin Kwon, Hye; ., . (International Journal of Engineering and Technology, 2018)
This study identified the development status and material development technology of mask packs in the beauty industry, which is recently receiving a global attention and designed a 4D mask pack enriched with hydrogels to meet the demand of the new era. This study also presented a next-generation mask model that has superior adhesion capability to facial curves. It was developed by applying hydrogels, a soft material similar to the extracellular matrix, to control mechanical properties of the mask pack for appropriate stiffness and swelling ratio. This development technology is considered to be a great help in creating a new convergence field of future beauty industry.Â